Achieving secure communication through pilot manipulation - Soltani, Morteza; Baykaş, Tunçer; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers, 2015)
Raising concerns about the security of wireless communication led researchers develop new concepts to keep information secret from eavesdroppers. Among them, physical layer security relies on the features of the wireless channels. Most of the work in physical layer security does focus on data transmission. On the other hand the focus of this work is to use manipulation of pilot tones to enhance communication security and to reduce eavesdroppers' ability to estimate the wireless channel. Particularly, we are introducing two novel algorithms, which manipulate pilot tones according to legitimate channels' phase and amplitude characteristics. Both algorithms decrease the channel estimation quality of the eavesdropper considerably, while the amplitude based algorithm provides high quality reception at the legitimate receiver. We provide resulting pilot error rates due to proposed algorithms. In addition, we show the effect of threshold selection to channel estimation quality both at the legitimate receiver and eavesdropper.
Keywords: Channel Estimation; Communication Secrecy; Eavesdropping; Physical Layer Security; Pilot Manipulation